Pattern of skin diseases in rural population: a cross sectional study at Medchal mandal, Rangareddy district, Telangana, India - Bommakanti, Janardhan; Pendyala, Pradeep (International Journal of Research in Medical Sciences, 2016)
Background: The skin diseases are affected by various factors. The rural population is more vulnerable because of illiteracy. Therefore an attempt has been made to screen the population of five villages to know pattern of skin diseases. Aims of the study were to assess the prevalence of skin diseases, determine the pattern of skin diseases in the study population in rural community of Medchal mandal and compare previous studies so that inferences can be drawn for the benefit of society. Methods: The study was aimed to include the total population of 5930 consisting of 5 villages. The present study was carried out during a period of one and half year in 5 villages of Medchal mandal. The total population of all the 5 villages comprises of 7726, out of which 5930 persons participated in the present study. In all villages house to house survey was done. A complete dermatological assessment of the study population was done and findings were recorded on the standard study proforma. Results: The total number of 5930 persons was screened during the period of study. Among which 1172 (19.76%) persons were noted to have skin diseases. out of which 533 (45.48%) were males and 639 (54.52%) were females. The majority of population with skin disease was in the age group of 31-40 years with 289 cases (24.65%) and least in 71-80 age groups with 7 cases (0.59%). The prevalence of Non-infectious diseases (705 cases, 60.15%) was more than that of Infectious diseases (467 cases, 39.85%). Among non-infectious conditions Eczema / Allergy was the common disease followed by Pigmentary disorders other conditions like alopecia areata, seborrheic dermatitis and senile xerosis, Papulosquamous disorders, acne and acneiform dermatoses, polymorphous light eruptions and bite and stings, Eczemas followed by lichen simplex chronicus and allergic contact dermatitis. Among infectious conditions, bacterial infections were most common diseases followed by parasitic infestations, fungal infections and viral infections. Among Bacterial infections, secondary Pyodermas followed by folliculitis, impetigo and furunculosis. Based on occupation the majority of population was in the students followed by farmers, labour other than agriculture, housewives and petty business. Based on education, the majority of population was in the primary group (class 1 to 5) followed by secondary (class 6 to 8) and high school and above. Conclusions: Based on the outcome of this study, the common skin problems existing in this area are to be carefully looked for and health education regarding the hygiene, nutrition and healthy life styles is to be stressed for better standard of living by the rural population.